Romance languages : a historical introduction - Alkire, Ti, 1961- (Cambridge University Press, 2010)
"Ti Alkire and Carol Rosen trace the changes that led from colloquial Latin to five major Romance languages, those which ultimately became national or transnational languages: Spanish, French, Italian, Portuguese, and Romanian. Trends in spoken Latin altered or dismantled older categories in phonology and morphology, while the regional varieties of speech, evolving under diverse influences, formed new grammatical patterns, each creating its own internal regularities. Documentary sources for spoken Latin show the beginnings of this process, which comes to full fruition in the medieval emergence of written Romance languages. This book newly distills the facts into an appealing program of study, including exercises, and makes the difficult issues clear, taking well motivated and sometimes innovative stands. It provides not only an essential guide for those new to the topic, but also a reliable compendium for the specialist"--